Perkembangan Model Integrasi Pendidikan dalam Hadist dan Penerapan - Elvi Yenti; Ilyas Husti; Nurhadi Nurhadi (At-Tajdid : Journal of Islamic Studies, 2022)
The phenomenon of the separation of general science, science and religion (dichotomies) has started in the Middle Ages and has continued until now. In order to form people who are faithful and pious and have noble character in accordance with the mandate of the Indonesian education law, there is a need for an educational integration model. Seeing this phenomenon, this paper aims to examine the development of the integration model of education in hadith and its application. The type of research used is a literature review. Based on the literature review collected, it was found that the absolute truth sources of knowledge are the Koran and Hadith, in both sources there is no dichotomy of science. All knowledge is the knowledge of Allah, in the hadith we find that it is obligatory to seek knowledge, there is no separation between general knowledge and religion, there is fardu a'in science and fard kifayah science. Fard'ain science is a science that studies fardhu'ain practices, while fardu-kifayah science is a science for fard-kifayah practices, such as science for medicine, pharmacy, astronomy, economics, political science and so on. It is found in the hadith that the model of integration of knowledge is to teach whatever knowledge the goal is for faith, love of Allah and heaven. Likewise the hadith in trade, the purpose of war is to get the pleasure of Allah and Islam is Rahmatanlil'alamin.